2015
DOI: 10.1200/jco.2014.58.5380
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Radiotherapy for Pathologic N2 Non–Small-Cell Lung Cancer Treated With Adjuvant Chemotherapy: A Review of the National Cancer Data Base

Abstract: Purpose To investigate the impact of modern postoperative radiotherapy (PORT) on overall survival (OS) for patients with N2 non–small-cell lung cancer (NSCLC) treated nationally with surgery and adjuvant chemotherapy. Patients and Methods Patients with pathologic N2 NSCLC who underwent complete resection and adjuvant chemotherapy from 2006 to 2010 were identified from the National Cancer Data Base and stratified by use of PORT (≥ 45 Gy). A total of 4,483 patients were identified (PORT, n = 1,850; no PORT, n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
156
7
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(173 citation statements)
references
References 26 publications
8
156
7
2
Order By: Relevance
“…Modest improvements in overall survival have been observed in patients receiving adjuvant chemotherapy; however, these patients never received pre-operative chemotherapy, therefore it is not directly comparable [10] . Post-operative radiotherapy is not routinely used for completely resected early stage lung cancer (I + II), although patients with N2 disease can be considered for it [11] .…”
Section: Discussionmentioning
confidence: 99%
“…Modest improvements in overall survival have been observed in patients receiving adjuvant chemotherapy; however, these patients never received pre-operative chemotherapy, therefore it is not directly comparable [10] . Post-operative radiotherapy is not routinely used for completely resected early stage lung cancer (I + II), although patients with N2 disease can be considered for it [11] .…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that the PORT-first strategy after surgery for stage IIIA (pN2) NSCLC patients did not compromise the clinical outcomes, and that the OS benefit of POCT given after PORT was observed. Since the OS was superior to that obtained in the historical series in which PORT was applied after POCT (3,9,12), the authors suggested that the use of PORT before rather than after POCT may have contributed to this improvement. Such conclusions obviously have their limitations, also acknowledged by the authors.…”
mentioning
confidence: 87%
“…Modern series of PORT show promising results with very low toxicity (3,(7)(8)(9). Population-based studies support the use of PORT also with adjuvant chemotherapy for pN2 patients, in contrast to pN0 and pN1 patients in whom PORT was associated with reduction of survival (10)(11)(12).…”
mentioning
confidence: 99%
“…The benefit of PORT for these patients had been controversial (9,10) until the results of the Lung ART study (11). However, a recent retrospective study and meta-analysis of PORT demonstrated that it had a positive effect (12,13).…”
Section: Editorialmentioning
confidence: 99%